PERSPEKTIF ALQUR’AN TENTANG PENDIDIKAN KARAKTER (PENDEKATAN TAFSIR MAUDHU’I) - HASAN ZAINI (Ta'dib, 2013)
Qur’an is a holly book that was revealed by Allah S.W.T to the prophet Muhammad (p.b.u.h) as guidances for human kind to live better in order to help them to get good part today and the day after. Qur’an is also as a direction (hudan) for people in general and obedient people (moslem) specifically, and it has been a medium to make it different between good and bad (al-furqan). As revelation, Qur’an discusses about faith, etiquette, moral value, and character. This study described Qur’an perspective of character education. Through character education, it is hoped that moslem people can apply it in line with Qur’an rules. Therefore, moslem people can achieve good personality (akhlatul-karimah dan Mmahmudah) and avoid something bad (mazmumah), even achieving demoralization.Kata Kunci: al-quran, pendidikan karakter, akhlak, etika dan moral